INTELIGENT BUILDING SYSTEM (IBS) AS A GREEN AND SMART APPROACH IN INDONESIA: BENEFIT, PROBLEM, AND CHALLENGE - S, Andi Harapan (Majalah Ilmiah UNIKOM, 2017)
Intelligent Building System (IBS) is a concept that elaborate architectural de-sign, interior design, mechanical and electrical in order to provide the mobility and ease of control and access from any direction and any time. The system is highly related to automation, where all the utility system in the building still can be operating without any people’s intervention, even if there are no people in-side of the building, the system will run in accordance with the program that we have created.IBS is not a new thing in Indonesia, it is a concept that has developed since a few years ago. The term of IBS is more popular as Smart Building System (SBS), where the concept has been applied in several buildings in Indonesia. But unfor-tunately, this concept was limited to office and commercial buildings, and only focused on a few major cities in Indonesia, such as Jakarta.In general, the concept of IBS in Indonesia is to help customers create within their projects an environment that maximizes the efficiency of its occupants while at the same time allow effective management of resources with minimum lifetime cost. With the benefits: 1) Capex and Opex Cost Efficiency, 2) Interac-tion of Systems, 3) End User and System Management Benefits, 4) Streamlined Design and Construction.But in reality, IBS is still rarely applied in Indonesia due to several factors, such as: 1) Lack of understanding of the importance of IBS system, 2) The high cost of IBS, 3) The system is still limited in big cities, especially Jakarta, 4) The opera-tional method and maintenance which is hard to do, 5) IBS is viewed by many stakeholders as a tool of commercial use only.Viewed from its benefits, the IBS is very useful and provides a high value, not only the matter of cost, but also environment and technology. These problems could be solved if the stakeholders of development sector in Indonesia can col-laborate to implement this system. Those mentioned could be the building own-ers, tenants, government, design consultants (including architects), contractors, and others.This paper discusses about the IBS within the context of green programs in In-donesia, also discusses about the benefits, problems and challenges through-out the implementation of this system in Indonesia.